Step
*
1
of Lemma
rv-compass-compass-lemma
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. a ≠ c
6. ↓∃p,q:ℝ^2. (((d(a;b) = d(a;p)) ∧ (d(c;d) = d(c;q))) ∧ (d(c;p) ≤ d(c;d)) ∧ (d(a;q) ≤ d(a;b)))
⊢ (d(b;a)^2 - d(d;c)^2) + d(a;c)^2^2 ≤ (r(4) * d(a;c)^2 * d(b;a)^2)
BY
{ ((D -1 THEN (Unhide THENA Auto)) THEN ExRepD) }
1
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. a ≠ c
6. p : ℝ^2
7. q : ℝ^2
8. d(a;b) = d(a;p)
9. d(c;d) = d(c;q)
10. d(c;p) ≤ d(c;d)
11. d(a;q) ≤ d(a;b)
⊢ (d(b;a)^2 - d(d;c)^2) + d(a;c)^2^2 ≤ (r(4) * d(a;c)^2 * d(b;a)^2)
Latex:
Latex:
1.  a  :  \mBbbR{}\^{}2
2.  b  :  \mBbbR{}\^{}2
3.  c  :  \mBbbR{}\^{}2
4.  d  :  \mBbbR{}\^{}2
5.  a  \mneq{}  c
6.  \mdownarrow{}\mexists{}p,q:\mBbbR{}\^{}2.  (((d(a;b)  =  d(a;p))  \mwedge{}  (d(c;d)  =  d(c;q)))  \mwedge{}  (d(c;p)  \mleq{}  d(c;d))  \mwedge{}  (d(a;q)  \mleq{}  d(a;b)))
\mvdash{}  (d(b;a)\^{}2  -  d(d;c)\^{}2)  +  d(a;c)\^{}2\^{}2  \mleq{}  (r(4)  *  d(a;c)\^{}2  *  d(b;a)\^{}2)
By
Latex:
((D  -1  THEN  (Unhide  THENA  Auto))  THEN  ExRepD)
Home
Index